Overview of Meta-Analyses of Five Non-pharmacological Interventions for Alzheimer's Disease - Wang, Liao-Yao; Pei, Jian; Zhan, Yi-Jun; Cai, Yi-Wen (Frontiers in Aging Neuroscience, 2020)
Background: Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive memory deficits, cognitive decline and spatial disorientation, which seriously endangers human health. The role of non-pharmacological interventions to treat AD has been reported in many meta analyses (MAs), but robust conclusions have not been made due to variations in the scope, quality and findings of these reviews. Objective: To provide an overview of existing evidence on the effects of non-pharmacological interventions in AD patients on three outcomes: mini-mental state examination (MMSE), activities of daily living (ADL) and Alzheimer’s disease assessment scale-cognitive section (ADAS-cog) by a review of existing MAs. Methods: The databases PubMed, Cochrane Library, Embase, and Web of Science were searched to collect MAs of non-pharmacological interventions for AD. Literature screening, data extraction, and quality assessment were independently conducted by 2 reviewers. We assessed the quality of MAs with the AMSTAR-2 tool, and assessed the evidence quality for significant outcomes using the grading of recommendations assessment, development and evaluation (GRADE) system. Results: We found ten eligible MAs which included between three (133 patients) and 15 randomized trials (1217 patients). Contains 5 non-pharmacological interventions, namely acupuncture therapy (40%), exercise intervention (30%), music therapy (10%), cognitive intervention (10%), repetitive transcranial magnetic stimulation(rTMS) (10%). All of the included MAs were of critically low quality to low quality with the AMSTAR-2 tool. Acupuncture therapy and exercise intervention show preliminary potential to improve ADL and MMSE. rTMS and acupuncture therapy show benefits in decreasing ADAs-cog. And there is some evidence of improved MMSE with cognitive intervention. All of these outcomes scored very low quality to moderate quality of evidence on the GRADE system. Conclusions: Non-pharmacological therapy has a promising prospect for the treatment of AD, but there is still a lack of high-quality evidence. In future, the quality of the original research needs to be improved and strict designed MA should be carried out in accordance with the methodological requirements.